-
Notifications
You must be signed in to change notification settings - Fork 0
/
proofs_new.tex
365 lines (332 loc) · 17.5 KB
/
proofs_new.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
\appendix
\section{Proofs}
\label{sec:proofs}
First we state some technical lemmas that will be used in the following proofs.
Define the Lambert function $W(x):\R\rightarrow\R$ as the one that satisfies the equality\footnote{For $x<0$ the Lambert function is multivalued. Hence, to avoid complication and because we only need positive arguments, we will define it only for positive values of $x$.}
\begin{equation}
\label{eq:lambert}
x=W(x) \exp \left(W(x)\right), \ \forall x\geq0.
\end{equation}
It satisfies the following properties.
%
\begin{lemma}
The Lambert function satisfies $0.6321 \log(x+1) \leq W(x) \leq \log(x+1), \forall x\geq0$.
\end{lemma}
%
\begin{proof}
We first prove the lower bound. From \eqref{eq:lambert} we have
\begin{align}
W(x) &= \log\left(\frac{x}{W(x)}\right) \label{eq:lm_lambert_1} \\
&= \log\left(\frac{x}{\log(x/W(x))}\right). \label{eq:lm_lambert_1b}
\end{align}
From the first equality, for any $a>0$, we get
\[
W(x) \leq \frac{1}{a\, e}\left(\frac{x}{W(x)}\right)^a
\]
that is
\begin{equation}
\label{eq:lm_lambert_2}
W(x) \leq \left(\frac{1}{a\, e}\right)^\frac{1}{1+a} x^\frac{a}{1+a}.
\end{equation}
Using \eqref{eq:lm_lambert_2} in \eqref{eq:lm_lambert_1}, we have
\begin{align*}
W(x)
\geq \log\left(\frac{x}{\left(\frac{1}{a\, e}\right)^\frac{1}{1+a} x^\frac{a}{1+a}}\right)
= \frac{1}{1+a}\log\left(a \, e\, x\right)~.
\end{align*}
Consider now the function $g(x)=\frac{x}{x+1} - \frac{b}{\log(1+b) (b+1)} \log(x+1), x\geq b$. This function has a maximum in $x^*=(1+\frac{1}{b}) \log(1+b)-1$, the derivative is positive in $[0,x^*]$ and negative in $[x^*,b]$. Hence the minimum is in $x=0$ and in $x=b$, where it is equal to $0$.
Using the property just proved on $g$, we have that for $x\leq b$, setting $a=\frac{1}{x}$, we have
\begin{align*}
W(x)
\geq \frac{x}{x+1} \geq \frac{b}{\log(1+b) (b+1)} \log(x+1)~.
\end{align*}
For $x>b$, setting $a=\frac{x+1}{e x}$, we have
\begin{align}
W(x)
&\geq \frac{e\,x}{(e+1) x + 1} \log(x+1) \geq \frac{e\,b}{(e+1) b + 1} \log(x+1)
\end{align}
Hence, we set $b$ such that
\[
\frac{e\, b}{(e+1)b + 1} = \frac{b}{\log(1+b) (b+1)}
\]
Numberically, $b=1.71825...$, so
\[
W(x) \geq 0.6321 \log(x+1)~. \qedhere
\]
For the upper bound, we use Theorem~2.3 in \cite{hoorfar2008inequalities}, that says that
\[
W(x) \leq \log\frac{x+C}{1+\log(C)}, \quad \forall x> -\frac{1}{e}, \ C>\frac{1}{e}.
\]
Setting $C=1$, we obtain the stated bound.
\end{proof}
\begin{lemma}
Define $f(\theta)= \beta \exp\frac{x^2}{2 \alpha}$, for $\alpha,\beta>0$, $x\geq0$. Then
\[
f^*(y)=y \sqrt{\alpha W\left(\frac{\alpha y^2}{\beta^2}\right)} - \beta \exp\left(\frac{W\left(\frac{\alpha y^2}{\beta^2}\right)}{2}\right).
\]
Moreover
\[
f^*(y) \leq y \sqrt{\alpha \log \left(\frac{\alpha y^2}{\beta^2} +1 \right)} - \beta.
\]
\end{lemma}
\begin{proof}
From the definition of Fenchel dual, we have
\begin{align*}
f^*(y)= \max_{x} \ x\, y - f(x) = \max_{x} \ x\, y - \beta \exp\frac{x^2}{2 \alpha} \leq x^*\,y -\beta
\end{align*}
where $x^*= \argmax_{x} x\, y - f(x)$. We now use the fact that $x^*$ satisfies $y = f'(x^*)$, to have
\begin{align*}
x^*=\sqrt{\alpha W\left(\frac{\alpha y^2}{\beta^2}\right)},
\end{align*}
where the function $W:\R_+ \rightarrow \R$ is the Lambert function that satisfies
\[
x=W(x) \exp \left(W(x)\right).
\]
Hence, to obtain an upper bound we need an upper bound to the Lambert function.
We use Theorem~2.3 in \cite{hoorfar2008inequalities}, that says that
\[
W(x) \leq \log\frac{x+C}{1+\log(C)}, \quad \forall x> -\frac{1}{e}, \ C>\frac{1}{e}.
\]
Setting $C=1$, we obtain the stated bound.
\end{proof}
\begin{lemma}[ {\citep[Example 13.7]{BauschkeC2011}} ]
Let $\phi:\R \rightarrow (-\infty, +\infty]$ be even. Then $(\phi \ast \norm{\cdot})^*=\phi^* \ast \norm{\cdot}$.
\end{lemma}
\begin{cor}
\label{cor:dual_exp_square}
Define $f(\theta)= \beta \exp\frac{\norm{\theta}^2}{2 \alpha}$, for $\alpha,\beta>0$. Then
\[
f^*(y) \leq \norm{\theta} \sqrt{\alpha \log \left(\frac{\alpha \norm{\theta}^2}{\beta^2} +1 \right)} - \beta.
\]
\end{cor}
\subsection{Proof of Theorem~\ref{theo:hilbert_reward}}
\begin{proof}
For simplicity denote by $f_t(\cdot)=f\left(\cdot, \{\norm{g_1}, \ldots, \norm{g_t}\}\right)$.
We will prove the thesis by induction. The base case is verified from the first point of Assumption~\ref{assumption:1-d_algo}. The, we assume that
\[
\epsilon + \sum_{t=1}^{n-1} \langle g_t, w_t \rangle \geq f_{n-1}\left( \norm{\sum_{t=1}^{n-1} g_t}\right),
\]
and we want to prove that
\[
\epsilon + \sum_{t=1}^{n} \langle g_t, w_t \rangle \geq f_{n}\left( \norm{\sum_{t=1}^{n} g_t}\right)~.
\]
We have that
\begin{align*}
\epsilon + \sum_{t=1}^{n} &\langle g_t, w_t \rangle - f_n\left( \norm{\sum_{t=1}^{n} g_t}\right) \\
&= \langle g_n, w_n \rangle + \epsilon + \sum_{t=1}^{n-1} \langle g_t, w_t \rangle - f_n\left( \norm{\sum_{t=1}^{n} g_t}\right)\\
&= \left(1+\frac{b_n}{\norm{\theta_{n-1}}}\langle \theta_{n-1},g_n \rangle \right)\left(\sum_{t=1}^{n-1} \langle g_t, w_t \rangle +\epsilon \right) - f_n\left( \norm{\sum_{t=1}^{n} g_t}\right)\\
&\geq \left(1+\frac{b_n}{\norm{\theta_{n-1}}}\langle \theta_{n-1},g_n \rangle \right) f_{n-1}\left( \norm{\sum_{t=1}^{n-1} g_t}\right) - f_n\left( \norm{\sum_{t=1}^{n} g_t}\right)\\
&= \left(1+\frac{b_n}{\norm{\theta_{n-1}}}\langle \theta_{n-1},g_n \rangle \right) f_{n-1}\left( \norm{\sum_{t=1}^{n-1} g_t}\right) - f_n\left( \norm{g_n + \sum_{t=1}^{n-1} g_t}\right)\\
%&= \left(1+\frac{b_n}{\norm{\theta_{n-1}}}\langle \theta_{n-1},g_n \rangle \right) f_{n-1}\left( \norm{\theta_{n-1}}\right) - f_n\left( \sqrt{\norm{\theta_{n-1}}^2 + \norm{g_n}^2 + 2 \langle \theta_{n-1}, g_n \rangle} \right)\\
&\geq \min_{r\in \{-1,1\}} \left(1+ r\, b_n \norm{g_n} \right) f_{n-1}\left( \norm{\theta_{n-1}}\right) - f_n\left(\left| \norm{\theta_{n-1}} + r \norm{g_n}\right|\right)\\
&= \min_{r\in \{-1,1\}} \left(1+ r\, b_n \norm{g_n} \right) f_{n-1}\left( \norm{\theta_{n-1}}\right) - f_n\left( \norm{\theta_{n-1}} + r \norm{g_n}\right)\\
&\geq 0,
\end{align*}
where the first inequality comes from the induction hypothesis, the second one using Lemma~8 in \citet{McMahanO14} and the last one by the hypothesis on the \ac{MBA}.
\end{proof}
\subsection{Proof of Theorem~\ref{theo:self_tune}}
\begin{proof}
The statement is readily proved using the inequality $a\,b \leq \frac{a^2}{\lambda} + \lambda b^2, \ \forall a,b\geq0, \lambda>0$ and Theorem~\ref{theo:online_to_batch}.
\end{proof}
\subsection{Proof of Theorem~\ref{theo:regret_pistol}}
\begin{proof}
From Theorem~\ref{theo:hilbert_reward} we have that
\[
\gain_n = \wealth_n - \epsilon \geq B n^{-C} \exp\left(\frac{\norm{\sum_{t=1}^n g_t}^2}{A n}\right)-D - \epsilon~.
\]
We now apply Theorem~\ref{thm:rrdual} and Corollary~\ref{cor:dual_exp_square} to have that
\[
Regret_n(u) \leq \norm{u} \sqrt{\frac{A T}{2} \log \left(\frac{\frac{A}{2} T^{2C+1} \norm{u}^2}{B^2} +1 \right)} - \frac{B}{T^{C}} + \epsilon+D~. \qedhere
\]
\end{proof}
\subsection{Proofs of Theorem~\ref{thm:oracle_fraction} and Theorem~\ref{thm:oracle_fraction_changing}}
We first state a couple of useful indentities.
For any $ 0\leq p < 1$
\[
D\left(\frac{1}{2}+\frac{p}{2}\middle\|\frac{1}{2}\right) = D\left(\frac{1}{2}-\frac{p}{2}\middle\|\frac{1}{2}\right)= \frac{1+p}{2} \log(1+p) + \frac{1-p}{2} \log(1-p).
\]
The extension for continuity of $D(\frac{1}{2}+\frac{p}{2}||\frac{1}{2})$ in $p=1$ is $\log(2)$.
Also,
\[
\left(\frac{n}{n-q}\right)^{n-q} \left(\frac{n}{q}\right)^{q} = 2^n \exp\left(-n D\left(\frac{q}{n}\middle\|\frac{1}{2}\right)\right),
\]
and
\begin{equation}
\label{eq:div_2}
\left(1+x\right)^\frac{1+x}{2} \left(1-x\right)^\frac{1-x}{2}= \exp\left( D\left(\frac{1}{2}+\frac{x}{2}\middle\|\frac{1}{2}\right) \right)
\end{equation}
Also, for any $-\frac{1}{2} \leq x\leq \frac{1}{2}$ we have
\[
\frac{x^2}{2} +\frac{x^4}{12}\leq D\left(\frac{1}{2}+\frac{x}{2}\middle\|\frac{1}{2}\right) \leq \frac{x^2}{2} + \frac{x^4}{5}.
\]
\begin{proof}[Proof of Theorem~\ref{thm:oracle_fraction}]
From the betting strategy we have
\[
\wealth_t=\wealth_{t-1} + w_t \, g_t = \wealth_{t-1} + \beta \, \wealth_{t-1} \, g_t = \wealth_{t-1} (1+\beta \, g_t)~.
\]
Hence
\[
\wealth_n=\epsilon \prod_{t=1}^n (1+\beta g_t) = \epsilon (1+\beta)^\frac{n+Z}{2} (1-\beta)^\frac{n-Z}{2},
\]
where $G=\sum_{t=1}^n g_t$.
It is easy to show that the maximum value of $\wealth_n$ w.r.t. $\beta$ is in $\beta=\frac{G}{n}$.
Hence, we have
\[
\wealth_n = \epsilon \left(1+\frac{G}{n}\right)^\frac{n+G}{2} \left(1-\frac{G}{n}\right)^\frac{n-G}{2}
= \epsilon \left[\left(1+\frac{G}{n}\right)^\frac{1+\frac{G}{n}}{2} \left(1-\frac{G}{n}\right)^\frac{1-\frac{G}{n}}{2}\right]^n
= \epsilon \exp\left( n \, D\left(\frac{1}{2}+\frac{G}{2n}\middle\|\frac{1}{2}\right) \right),
%\leq \epsilon \exp \left(\frac{Z^2}{2 n} + \frac{Z^4}{5 n^3}\right),
\]
where in the last equality we used \eqref{eq:div_2}.
%or
%\[
%\frac{x^2}{2} +\frac{x^4}{12}\leq \frac{1+x}{2} \log(1+x) + \frac{1-x}{2}\log(1-x) \leq \frac{x^2}{2} + \log(2)-.5
%\]
%where the lhs is given by Taylor expansion.
\end{proof}
The following tail bound for Binomial variables is from~\cite{Orabona13} and we report here the proof for completeness.
\begin{theorem}
\label{lemma:bin}
Let $n\geq2$ an even number of Bernoulli random variables $b_i$. Then for any $k \in \Nat_0$ such that $k\leq \frac{1}{2}n-1$, we have
\[
P\left( \sum_{i=1}^n b_i \geq \frac{1}{2} n + k\right)
\geq \frac{\exp\left(-n\, D\left(\frac{1}{2}+\frac{k}{n}\middle\|\frac{1}{2}\right)\right)}{2 \exp\left(\frac{1}{6}\right)} \frac{\sqrt{2 \pi}}{(\pi-1)y+\sqrt{y^2+2 \pi}},
\]
where $y=\frac{2 k}{\sqrt{n}}$.
\end{theorem}
\begin{proof}
We use Theorem~2 in \cite{McKay1989}, that specialized to our case says that
\begin{equation}
\label{eq:bin_1}
P\left( \sum_{i=1}^n b_i \geq \frac{1}{2} n + k \right)
\geq \sqrt{n} \binom{n-1}{ \frac{1}{2} n + k -1} 2^{-n} \frac{Q(y)}{\phi(y)},
\end{equation}
where $\phi(x)$ is the unit variance, zero mean Gaussian, $\frac{1}{\sqrt{2 \pi}} \exp(-\frac{x^2}{2})$ and $Q(x)$ is its CDF, $\int_{x}^{+\infty} \phi(u) du$.
We start lower bounding the ratio $\frac{Q(y)}{\phi(y)}$. Using the inequality in \cite{Boyd59}, that says
\[
\frac{Q(y)}{\phi(y)}
= \exp\left(\frac{x^2}{2}\right) \int_{x}^{+\infty} \exp\left(-\frac{t^2}{2}\right) dt
\geq \frac{\pi}{(\pi-1)x+\sqrt{x^2+2 \pi}}.
\]
To bound the binomial coefficient we make use of the following Stirling approximation, for any $n\geq 1$,
\[
\sqrt{2 \pi n} n^n \exp(-n) < n! < \exp\left(\frac{1}{12}\right)\sqrt{2 \pi n} n^n \exp(-n)~.
\]
Hence, for any $n \geq 2$ and $1\leq q \leq n-1$, after some algebra we obtain
\begin{align*}
{n \choose q}
&\geq \frac{1}{\exp\left(\frac{1}{6}\right) \sqrt{2 \pi}} \left(\frac{n}{n-q}\right)^{n-q} \left(\frac{n}{q}\right)^{q} \sqrt{\frac{n}{q(n-q)}} \\
&\geq \frac{1}{\exp\left(\frac{1}{6}\right) \sqrt{2 \pi}} 2^n \exp\left(-n D\left(\frac{q}{n}\middle\|\frac{1}{2}\right)\right) \sqrt{\frac{n}{q(n-q)}}.
\end{align*}
where in the equality we used the definition of $D\left(\cdot\middle\|\cdot\right)$.
Also, we have
\begin{equation}
\label{eq:bin_3}
{n-1 \choose \frac{1}{2} n + k - 1} = {n \choose \frac{1}{2} n + k} \left(\frac{1}{2} + \frac{k}{n}\right) .
\end{equation}
Putting together \eqref{eq:bin_1}-\eqref{eq:bin_3}, and using the definition of $y$ we have
\begin{align*}
P\left( \sum_{i=1}^n b_i \geq \frac{1}{2} n + k \right)
&\geq \frac{1}{\exp\left(\frac{1}{6}\right) \sqrt{2 \pi}} \exp\left(-n\, D\left(\frac{1}{2}+\frac{k}{n}\middle\|\frac{1}{2}\right)\right) \sqrt{\frac{\frac{1}{2} + \frac{k}{n}}{\frac{1}{2}-\frac{k}{n}}} \frac{Q(y)}{\phi(y)} \\
&\geq \frac{1}{\exp\left(\frac{1}{6}\right) \sqrt{2 \pi}} \exp\left(-n\, D\left(\frac{1}{2}+\frac{k}{n}\middle\|\frac{1}{2}\right)\right) \frac{\pi}{(\pi-1)y+\sqrt{y^2+2 \pi}}. \qedhere
\end{align*}
\end{proof}
We can now prove Theorem~\ref{thm:oracle_fraction_changing}.
\begin{proof}[Proof of Theorem~\ref{thm:oracle_fraction_changing}]
First observe that, even knowing all the outcomes of $g_t$, we cannot gain more than $\epsilon 2^n$, simply betting on each round all the money on the correct outcome.
Then, for a specific function $g(\cdot,\cdot)$ that grows in the first argument, we will show that
\begin{align*}
\min_{|\sum_{t=1}^n g_t| \geq 2 k} \sum_{t=1}^n w_t g_t
\leq \epsilon \, g(k,n), \ \forall 0 \leq k \leq n-1.
\end{align*}
When $k=n/2$, we cannot gain more than $\epsilon 2^n$, this is why we can safely consider only $0\leq k\leq n/2-1$.
From this we will infer that
\begin{align*}
\min_{g_t} \sum_{t=1}^n w_t g_t - \epsilon\min\left(g\left(\frac{|\sum_{t=1}^n g_t|}{2},n\right),2^n\right) \leq 0,
\end{align*}
that implies the stated inequality.
Set $r_t$ as independent random variable that assumes the value of 1 with probability 0.5 and -1 with probability 0.5.
Hence, we have that $\E[ \sum_{t=1}^n w_t r_t ]=0$, and also $\sum_{t=1}^n w_t r_t \geq -\epsilon$ because we never lose more than the initial amount of money.
Hence we have
\begin{align*}
\min_{|\sum_{t=1}^n g_t| \geq 2 k} \sum_{t=1}^n w_t g_t
\leq \E\left[\sum_{t=1}^n w_t r_t \bigg| \left|\sum_{t=1}^n r_t\right| \geq 2 k\right], \ \forall 0 \leq k \leq n-1.
\end{align*}
For any $k\geq 0$, it follows that
\begin{align*}
0&=\E\left[\sum_{t=1}^n w_t r_t \right]
= \E\left[\sum_{t=1}^n w_t r_t \bigg| \left|\sum_{t=1}^n r_t \right|< 2 k\right] P\left(\left|\sum_{t=1}^n r_t\right|< 2k \right)\\
&\qquad+\E\left[\sum_{t=1}^n w_t r_t \bigg| \left|\sum_{t=1}^n r_t \right| \geq 2 k\right] P\left(\left|\sum_{t=1}^n r_t\right|\geq 2 k\right) \\
&=\E\left[\sum_{t=1}^n w_t r_t \bigg| \left|\sum_{t=1}^n r_t \right|< 2 k\right] \left(1-P\left(\left|\sum_{t=1}^n r_t\right|\geq 2 k\right)\right)\\
&\qquad+\E\left[\sum_{t=1}^n w_t r_t \bigg| \left|\sum_{t=1}^n r_t \right| \geq 2 k\right] P\left(\left|\sum_{t=1}^n r_t\right|\geq 2 k\right) \\
&\geq -\epsilon \left(1-P\left(\left|\sum_{t=1}^n r_t\right|\geq 2 k\right)\right)+\E\left[\sum_{t=1}^n w_t r_t \bigg| \left|\sum_{t=1}^n r_t\right| \geq 2 k\right] P\left(\left|\sum_{t=1}^n r_t \right|\geq 2 k\right),
\end{align*}
hence
\begin{align*}
\E\left[\sum_{t=1}^n w_t r_t \bigg| \left|\sum_{t=1}^n r_t\right| \geq 2 k\right]
&\leq \frac{\epsilon}{P\left(\left|\sum_{t=1}^n r_t\right|\geq 2 k\right)} -\epsilon
= \frac{\epsilon}{2 P\left(\sum_{t=1}^n r_t \geq 2 k\right)} -\epsilon\\
&= \frac{\epsilon}{2 P\left(\sum_{t=1}^n \frac{r_t + 1}{2} \geq \frac{1}{2}n+ k \right)}-\epsilon.
\end{align*}
Notice that $\frac{r_t + 1}{2}$ are Bernoulli random variables.
Using Theorem~\ref{lemma:bin}, we have
\begin{align*}
\E\left[\sum_{t=1}^n w_t r_t \bigg| \left|\sum_{t=1}^n r_t\right| \geq 2 k\right]
&\leq \epsilon \left(\exp\left(\frac{1}{6}\right)\sqrt{2 \pi}\frac{2k}{\sqrt{n}} +2\exp\left(\frac{1}{6}\right)-1\right)\exp\left(n \, D\left(\frac{1}{2}+\frac{k}{n}\middle\|\frac{1}{2}\right)\right)~. \qedhere
\end{align*}
\end{proof}
\subsection{Proof of Theorem~\ref{theo:cocob}}
\begin{proof}
We want to prove that, for any $t$
\[
(1+b_t z_t) \epsilon \exp\left( F(x,\delta+\sum_{i=1}^{t-1} z_i) - \sum_{i=1}^{t-1} \frac{z_i}{a (\delta+\sum_{j=1}^{i-1} z_j)}\right)
\geq \epsilon \exp\left(F(x+z_t,\delta+\sum_{i=1}^{t} z_i) - \sum_{i=1}^{t} \frac{z_i}{a (\delta+\sum_{j=1}^{i-1} z_j)}\right),
\]
where $F(x,G)= G \, D(\frac{1}{2}+\frac{x}{2 G}||\frac{1}{2})$.
The above is equivalent to prove
\[
\ln(1+b_t z_t) + F(x,\delta+\sum_{i=1}^{t-1} z_i)- \sum_{i=1}^{t-1} \frac{z_i}{a (\delta+\sum_{j=1}^{i-1} z_j)}
\geq F(x+z_t,\delta+\sum_{i=1}^{t} z_i)- \sum_{i=1}^{t} \frac{z_i}{a (\delta+\sum_{j=1}^{i-1} z_j)}~.
\]
Denote by $\sg_{t-1}=\sum_{i=1}^{t-1} z_i$ and consider the function
\[
\phi(z)=-\log(1+b_t z) + F(x+z,\sg_{t-1} + |z|)~.
\]
Assume that $\phi(z)$ is piece-wise convex on $[-\infty,0]$ and $[0,\infty]$. Hence, we have that
\begin{align*}
&\phi(z) \leq \phi(0)+z (\phi(1)-\phi(0)), \forall 0 \leq z\leq 1\\
&\phi(z) \leq \phi(0)+z (\phi(0)-\phi(-1)), \forall -1 \leq z\leq 0~.
\end{align*}
Also, we set $b_t$ such that $\phi(1)=\phi(-1)$, that is
\[
b_t = \frac{\exp(A_{t-1})-1}{\exp(A_{t-1})+1},
%= 2 \, S\left(\frac{4 x}{a (\sg_{t-1} + 1)}\right)-1
\]
where $A_{t-1}=F(x+1,\sg_{t-1} + 1)-F(x-1,\sg_{t-1} + 1)$.
Hence we have
\[
\phi(z) \leq \phi(0)+ |z| (\phi(1)-\phi(0)), \forall -1 \leq z\leq 1,
\]
that is
\begin{align*}
F(x,\sg_{t-1})-F(x+z,\sg_{t-1}+|z|) + \log(1+b_t z_t)
& = \phi(0) - \phi(z) \\
& \geq |z| \left(\phi(0) - \phi(1)\right) \\
&= |z| \left(F(x,\sg_{t-1}) - F(x+1,\sg_{t-1}+1) + \log(1+b_t)\right), \forall -1 \leq z\leq 1~.
\end{align*}
Using this relation we have that
\begin{align*}
&-F(x+z,\sg_{t-1}+|z|) + F(x,\sg_{t-1})+\log(1+b_t z_t)-\sum_{i=1}^{t-1} \frac{|z_i|}{a (\sg_{i-1} + 1)} \\
&\qquad \geq |z_t| \left(F(x,\sg_{t-1}) - F(x+1,\sg_{t-1}+1) + \log(1+b_t)\right) - \sum_{i=1}^{t-1} \frac{|z_i|}{a (\sg_{i-1} + 1)} \\
&\qquad = |z_t| \left(F(x,\sg_{t-1}) - F(x+1,\sg_{t-1}+1) + \log(1+\frac{\exp(A_{t-1})-1}{\exp(A_{t-1})+1})\right) - \sum_{i=1}^{t-1} \frac{|z_i|}{a (\sg_{i-1} + 1)}~.
%&\qquad = |z_t| \left(\frac{(\sg_{t-1} + 1) x^2 - (x^2+2 x )\sg_{t-1} }{a \sg_{t-1}(\sg_{t-1} + 1)} + \log(1+b_t)\right) - \sum_{i=1}^{t} \frac{|z_i|}{a (\sg_{i-1} + 1)}\\
%&\qquad = |z_t| \left(\frac{x^2}{a \sg_{t-1}(\sg_{t-1} + 1)}-\frac{2 x}{a (\sg_{t-1} + 1)} + \log(1+b_t)\right) - \sum_{i=1}^{t} \frac{|z_i|}{a (\sg_{i-1} + 1)}~.
\end{align*}
If $A_{t-1}<0$, that is $F(x+1,\sg_{t-1}+1) \leq F(x-1,\sg_{t-1}+1)$, we have that
\begin{align*}
&F(x,\sg_{t-1}) - F(x+1,\sg_{t-1}+1) + \log(1+\frac{\exp(A_{t-1})-1}{\exp(A_{t-1})+1})\\
&\qquad = F(x,\sg_{t-1}) - F(x-1,\sg_{t-1}+1) + F(x-1,\sg_{t-1}+1) - F(x+1,\sg_{t-1}+1) + \log(1+\frac{\exp(A_{t-1})-1}{\exp(A_{t-1})+1})\\
&\qquad \geq F(x,\sg_{t-1}) - F(x-1,\sg_{t-1}+1) -A_{t-1} + \log(1+\frac{\exp(A_{t-1})-1}{\exp(A_{t-1})+1})\\
\end{align*}
Consider the function $\phi(x)=\log(1+\frac{\exp(x)-1}{\exp(x)+1})$. We have $\phi(-x)=\phi(x)-x$.
\end{proof}